Cardiac diagnoses, procedures, and healthcare utilisation in inpatients with Ellis–van Creveld syndrome. (29th October 2013) - O'Connor, Matthew J.; Tang, Xinyu; Collins, R. Thomas
Abstract Introduction Ellis–van Creveld syndrome is a rare condition associated with a very high incidence of congenital malformations of the heart. Prior reports have suggested increased morbidity and mortality following surgery for congenital malformations of the heart in patients with Ellis–van Creveld syndrome. Materials and methods The Pediatric Health Information System database, an administrative database containing data from 43 free-standing paediatric hospitals in North America, was queried to search for patients with the diagnostic code for Ellis–van Creveld syndrome between 2004 and 2011. Those patients who underwent cardiac procedures were compared with those who did not with respect to measures of healthcare utilisation. Results A total of 138 admissions occurred in 93 patients with Ellis–van Creveld syndrome during the study period. Of these, 74% had an underlying diagnosis of congenital malformations of the heart. Half of the patients in the sample underwent a cardiac surgical or interventional catheterisation procedure. Patients who underwent a cardiac procedure had a longer hospital length of stay, higher incidence of intensive care unit admission, and higher total and per day hospital charges than patients who did not undergo cardiac surgery during admission. Conclusions In a large group of inpatients with Ellis–van Creveld syndrome, the prevalence of congenital malformations of the heart was similar to that reported in prior studies. Cardiac surgical and interventional procedures appear to drive a substantial portion of healthcare utilisation in these patients.